Experimental study of spray characteristics of biodiesel derived from waste cooking oil - Mohan, Balaji; Yang, Wenming; Tay, Kun Lin; Yu, Wenbin (Energy conversion and management, 2014)
•B20 and diesel exhibit similar spray tip penetration and angle.•Change in orientation of spray shapes observed with different fuels.•B100 shows poor air fuel mixing compared to B20 and diesel.•Diesel shows higher equivalence ratio compared to B20 and B100. In this study, the fuel spray characteristics and air-fuel mixing process of waste cooking oil biodiesel (B100) and its blend with diesel (B20) were investigated and compared with diesel fuel. Spray characteristics such as spray tip penetration, spray angle, spray velocity and spray morphology were investigated under high injection and ambient pressure conditions using a constant volume spray chamber. The air-fuel mixing process was analysed using empirical relations like fuel volume, mass of air entrained within the spray and equivalence ratio. The results shows that B100 has higher spray tip penetration and velocity but narrow spray angles due to high viscosity and large momentum possessed by B100 compared to B20 and diesel fuels. The deviation in spray tip penetration reduces under high ambient pressure. The spray angle shows no change under various injection pressures; however it increases significantly under high ambient pressure. The spray shape is affected by the cavitation inside the injector nozzle holes. The fuel volume and amount of air entrainment within the spray showed that B100 exhibits poor air-fuel mixing compared to B20 and diesel fuels. Nevertheless, the equivalence ratio along the axial direction of spray reveals that the B100 has lean equivalence ratio compared to B20 and diesel fuel due to the presence of inherent oxygen content in its structure. A numerical simulation was conducted using new hybrid spray model implemented in KIVA4 and found that the results obtained from the simulation were in good agreement with the empirical results calculated from the experiments.